Centeredness Theory: Understanding and Measuring Well-Being Across Core Life Domains - Bloch-Jorgensen, Zephyr T.; Cilione, Patrick J.; Yeung, William W. H.; Gatt, Justine M. (Frontiers in Psychology, 2018)
Background: Centeredness Theory (CT) is proposed as a new mental health paradigm that focuses on well-being at a systems-level, across the core life domains of the self, the family unit, relationships, community, and work. The current studies aimed to validate the psychometric properties of a new scale that measures Centeredness Theory against existing well-being and mental health measures. Methods: Study 1 included 488 anonymous online respondents (46% females, 28% males, 25% unknown with median age between 31-35 years) across 38 countries who completed the CT scale. Study 2 included 49 first-year psychology students (90% females, mean age of 19 years) from Sydney Australia that completed the CT scale and other well-being and mental health questionnaires at baseline and 2-weeks follow-up. Results: Exploratory and confirmatory factor analyses resulted in a refined 60-item CT scale with 5 domains, each with 4 sub-domains. The CT scale demonstrated good internal consistency reliability and test-retest reliability, and showed evidence of convergent validity against other well-being measures (e.g., COMPAS-W Wellbeing Scale, SWLS scale and Ryff’s Psychological Well-being scale). Conclusions: The CT scale appears to be a reliable measure of well-being at a systems-level. Future studies need to confirm these findings in larger heterogeneous samples.